Serum metabolic profiling of oocyst-induced Toxoplasma gondii acute and chronic infections in mice using mass-spectrometry - Zhou, Chun-Xue; Cong, Wei; Chen, Xiao-Qing; He, Shen-Yi; Elsheikha, Hany M.; Zhu, Xing-Quan (Frontiers Media, 2018)
Toxoplasma gondii is an obligate intracellular parasite causing severe diseases in immunocompromised individuals and congenitally infected neonates, such as toxoplasmosis encephalitis and toxoplasmic chorioretinitis. This study aimed to determine whether serum metabolic profiling can (i) identify metabolites associated with oocyst-induced T. gondii infection and (ii) detect systemic metabolic differences between T. gondii -infected mice patients and controls. We performed the first global metabolomics analysis of mice serum challenged with 100 sporulated T. gondii Pru oocysts (Genotype II). Sera from acutely infected mice (11 days post-infection, dpi), chronically infected mice (33 dpi) and control mice were collected and analysed using LC-MS/MS platform. Following False Discovery Rate filtering, we identified 3871 and 2825 ions in ESI + or ESI − mode, respectively. Principal Component Analysis (PCA) and Partial Least Squares Discriminant Analysis (PLS -DA) identified metabolomics profiles that clearly differentiated T. gondii -infected and -uninfected serum samples. Acute infection significantly influenced the serum metabolonme. Our results identified common and uniquely perturbed metabolites and pathways. Acutely infected mice showed perturbations in metabolites associated with glycerophospholipid metabolism, biosynthesis of amino acid, and tyrosine metabolism. These findings demonstrated that acute T. gondii oocyst induces a global perturbation of mice serum metabolonme, providing new insights into the mechanisms underlying systemic metabolic changes during early stage of T. gondii oocyst infection.